Teachers’ Multilingualism Belief and Practice in Indonesian EFL Classroom - Alam Djati Nugraheni; Joko Nurkamto; Kristian Adi Putra (STAI Hubbulwathan Duri, 2023)
This narrative case study aimed to explore EFL teachers' beliefs and practices regarding multilingualism in Indonesia. The data for this study was collected through observations and interviews with three EFL teachers in a public junior high school in Indonesia who were chosen, based on purposive sampling, who have experience in EFL teaching and have graduated from the relevant study program. The collected data were analyzed using thematic analysis. This study revealed that teachers' beliefs and practices are in line. They used multilingualism in EFL teaching, namely Indonesian, the local language, and English as the language of instruction. They used those languages to make their students easier to understand. Moreover, multi-language is used because not all students have good English, and it also aims to maintain students' indigenous languages. Generally, this study concluded that EFL teachers' beliefs are a factor that influences their classroom language policy, and teachers' attitudes toward multilingualism have an impact on students' language practices. Hopefully, this research can improve the teacher's understanding and provide a reference for relevant future research. Further research could look at more than three EFL teachers and use the other technique for collecting data and analyzing documents from teachers and students to gain a better understanding.